Effects of Syzygium aromaticum (clove) Extract on the Acquisition and Expression of Morphine-Induced Conditioned Place Preference in Swiss Albino Mice: an In vivo, In Silico Approach (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Empirical findings have demonstrated that the application of an N-Methyl-D-aspartate (NMDA) receptor antagonist effectively prevents the formation of morphine-induced location preference. Eugenol, the primary constituent found in the extract of S. aromaticum (SA), exhibits notable efficacy in traversing the blood-brain barrier and possesses inhibitory properties against the metabotropic NMDA receptor. This study aimed to evaluate the actions of the hydro-alcoholic extract of S. aromaticum on the acquisition and expression of morphine-induced conditioned place preference (CPP) in mice, followed by in silico studies. The conditioned place preference (CPP) test was used for investigating addictive-seeking behavior. Morphine (5 mg/kg) was used to produce CPP, and saline was used as a control. Morphine significantly increased the preference scores on the drug-paired side (p 0.3). On the basis of our in vivo trials and in silico report, we settled that the acquisition effect of S. aromaticum might be due to the antioxidant and antagonistic properties of eugenol to NMDA receptor. It would be reasonable to conduct mechanistic research in the forthcoming days to elucidate the underlying mechanisms utilizing various methodologies.Dhaka Univ. J. Pharm. Sci. 23(1): 77-92, 2024 (June)